Breaking Images (Open Book Publishers, 2025)
Mathematics is an activity—something we do—not just something inert that we study. This rich collection begins from that premise to explore the various social influences, institutional forces and lived realities that shape and mould the study and practice of mathematics, and are moulded by it in turn. These twenty-one essays explore questions of mathematics as a topic of philosophy, but also the nature and purpose of mathematics education and the role of mathematics in moulding citizens. It challenges the biases and prejudices inherent within uninformed histories of mathematics, including problems of white supremacy, the denial of cultural difference and the global homogenization of teaching methods. In particular, the book contrasts the effectiveness of mathematics and science in modelling physical phenomena and solving technical problems with its ineffectiveness in modelling social phenomena and solving human problems, and urges us to consider how mathematics might better meet the urgent crises of our age. The book addresses anybody who is interested in reflecting on the role of mathematics in society from different perspectives. It allows mathematicians to ponder about the cultural connections of mathematics and provides new perspectives for philosophical, sociological and cultural studies of mathematics. Because of the book’s emphasis on education in mathematics, it is especially interesting for mathematics teachers and teacher educators to challenge their understanding of the subject.